A comparison between inverse dynamics skeletal and muscular models. (1st January 2012) - Mari, Silvia; Pennestrì, Ettore; Trebbi, Martina; Nappi, Francesco; Rughi, Diego
This investigation has the purpose of developing and cross-validating algorithms and software tools for quantitative ergonomic analyses of workers movements. In particular, the results from a skeletal inverse dynamics model are directly compared with those obtained from a muscular model herein proposed. Both models rely upon experimentally gathered kinematic and electromyography data. The 2D skeletal model is based on a multibody dynamics formulation. The software implementation can perform both kinematic and inverse dynamic analyses. Kinematic input data required by the model have been collected using an optoelectronic human motion capture system. The kinematics of the model has been compared with experimentally collected data. The muscular electromyography (EMG)-assisted model discussed is particularly suitable for biarticular muscles. Joint torques, muscular forces and powers can be also estimated. The inputs required by this model have been collected recording surface electromyographic signals and using some kinematic output from the skeletal model. The results from mathematical models have been compared for cross-validation, and their adequacy for ergonomy analyses assessed.